Elevated, FcεRI‐dependent MRGPRX2 expression on basophils in chronic urticaria - Ewa A. Bartko; Jesper Elberling; Lars H. Blom; Lars K. Poulsen; Bettina M. Jensen (Wiley, 2023)
Abstract Background Chronic urticaria (CU) is a skin condition driven by mast cells and basophils. The exact responsiveness profile of these cells, especially regarding the anti‐IgE treatment, Omalizumab, is not fully investigated. We sought to characterize the surface activation profile of basophils in CU during Omalizumab treatment and their responsiveness to IgE and non‐IgE stimulation. Methods Whole blood basophils from 11 CU patients and 10 healthy controls were stimulated with either medium, anti‐IgE, fMLP, C5a, or Substance P for 30 min and characterized by flow cytometry. Results CU patients showed a broad range of basophil count as opposed to healthy subjects. An increased number of unstimulated CD69+ (p = 0.05), but not CD63+ basophils was observed in CU groups in comparison to healthy. The expression of CD203c and CD200R were comparable between all groups, whilst the FcεRI was reduced with the treatment. Both IgE and non‐IgE mediated stimulations upregulated CD63, CD203c and CD200R, but not CD69 in all groups, however, no difference between the groups was observed. Among unstimulated basophils, expression of MRGPRX2 was higher in CU patients after Omalizumab treatment than in the healthy group (2.4% vs. 1.5%, p = 0.01). The anti‐IgE stimulation increased the number of MRGPRX2‐expressing basophils in the CU group before and after omalizumab as compared to the healthy (p = 0.003; p = 0.005). The fMLP and C5a stimulations showed a similar effect to the IgE‐mediated stimulation. The MRGPRX2 ligand, Substance P did not activate basophils. Conclusion CU basophils show increased expression of MRGPRX2 after IgE and non‐IgE stimulation.